Using of articulators in the construction Of crown and bridges work in Baghdad:(A survey study) (Mustansiria Dental Journal, 2018)
Articulators are surrounded by an aura of mystery, but at the end of the day they are a tool to help a dentist to give his patient a successful restoration, saving time money and hassle.This study was conducted to obtain data from which some preliminary judgments could be made regarding the articulators being used for fixed partial denture laboratory procedure in dental practice. Data were collected from a questionnaire sent to 15 fifteen dental laboratories (which performed fixed prostheses only) in Baghdad, the number of the technicians employed by the laboratory were 55, the number of the dentists deal with the specified laboratory were 524 dentists including (Professional dentists 180, Post-graduate dental students 46 and Junior dentists 298), the type of the fixed-prosthodontics (cast metal, PFM, and All-ceramic) and the percentage of each type of work, the percentage of using articulators and the type of the articulators and the percentage of there uses included (simple hinge, semi-adjustable and fully-adjustable).Results showed that the percentage of articulators being used was 16.66% in comparison to the percentage of hand articulation 83.33% distributed as 99.66% used simple articulators, 0.33% semi-adjustable articulators and 0% for fully adjustable articulators.